2015
DOI: 10.1088/0953-8984/27/5/055701
|View full text |Cite
|
Sign up to set email alerts
|

Electron-boson spectral density of LiFeAs obtained from optical data

Abstract: Abstract. We analyze existing optical data in the superconducting state of LiFeAs at T = 4 K, to recover its electron-boson spectral density. A maximum entropy technique is employed to extract the spectral density I 2 χ(ω) from the optical scattering rate. Care is taken to properly account for elastic impurity scattering which can importantly affect the optics in an s-wave superconductor, but does not eliminate the boson structure. We find a robust peak in I 2 χ(ω) centered about Ω R ∼ = 8.0 meV or 5.3 k B T c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 54 publications
1
15
0
Order By: Relevance
“…Since FeAs-compounds have multibands the compounds can be analyzed approximately with two Drude components as in Dai et al paper8, which corresponds to the two-component analysis for cuprates. The one-component (or extended Drude model) analysis has been applied to Fe-pnictide systems121314 with a single band approximation even though the material systems have multiband characteristics. To resolve the multiband issue one should develop a new method including the multiband nature.…”
mentioning
confidence: 99%
“…Since FeAs-compounds have multibands the compounds can be analyzed approximately with two Drude components as in Dai et al paper8, which corresponds to the two-component analysis for cuprates. The one-component (or extended Drude model) analysis has been applied to Fe-pnictide systems121314 with a single band approximation even though the material systems have multiband characteristics. To resolve the multiband issue one should develop a new method including the multiband nature.…”
mentioning
confidence: 99%
“…Near normal incidence reflectivity from 20 to 6 000 cm −1 was measured on Bruker IFS113 and IFS66v spectrometers at 5,10,15,20,25,50,100,200, and 300 K. The absolute reflectivity of the sample was obtained with an in situ gold overfilling technique [17]. The reTypeset by REVT E X flectivity has an absolute accuracy better than 0.5% and a relative accuracy better than 0.1%.…”
Section: Methodsmentioning
confidence: 99%
“…They described their data in the framework of multiple superconducting gaps, and found two fully open, gaps at 2∆ 0 = 3.2 meV and 2∆ 0 = 6.3 meV. These data were further analyzed in terms of Eliashberg theory [15]. STM also finds two homogeneous nodeless gaps, but with values twice as large [5].…”
Section: Introductionmentioning
confidence: 96%
“…We used known superconducting gaps of the two materials [32,33]: two superconducting gaps of BKFA are 5.5 meV (∆ 0,1 ) and 12.5 meV (∆ 0,2 ) [32] and two SC gaps of LiFeAs are 1.6 meV and 3.15 meV [33]. We took the sharp mode frequencies from reported values by inelastic neutron scattering study of BKFA [39] and scanning tunneling [40], and optical spectroscopy studies [24]. The obtained I 2 χ(ω) are shown in Fig.…”
Section: Applications To Real Systemsmentioning
confidence: 99%
“…Many optical studies have been successfully done on cuprate systems for delving and exposing the electron-boson spectral density function [7,16,17,18,19,20,21]. Recently some optical studies [22,23,24] have been done on iron-pnictides to obtain the electron-boson density spectrum by using a singleband approximation method, which has been used for studying cuprates. Charnukha et al [25] have tried to include the multiband coupling information obtained from specific heat measurement study of the same material [26] and showed that observed unusual structure of the optical conductivity in superconducting state can be ascribed to spinfluctuation-assisted process.…”
Section: Introductionmentioning
confidence: 99%